STRUKTUR PENYAJIAN MALAM BAINAI PADA PESTA PERKAWINAN DI KOTA PADANG - Sylvia Sylvia; Syahrel Syahrel; Marzam Marzam (FBS Universitas Negeri Padang, 2014)
Abstract This research was intended to describe the presentation structure of Malam Bainai a wedding ceremony in Kelurahan Kubu Dalam Parak Karakah Kecamatan Padang Timur Kota Padang. This was a qualitative research which used descriptive analysis approach. The procession of Malam Bainai consisted of three main parts including Bamandi-Mandi, Maniti Kain Kuniang, and Bainai. In bainai procession, inai was applied by bako, and the sisters of the bride’s mother, the wife of the bride’ uncle or female family coming in that procession. Kata kunci: Malam Bainai, Bamandi-Mandi, Maniti Kain Kuniang, Bainai